Sistem Informasi Simulasi Dan Penilaian Kredit Skoring Berbasis Website Pada PT. Bank Perkreditan Rakyat Dana Nusantara Kota Tanjungpinang - Abdulrahmad, Abdulrahmad; Zulfachmi, Zulfachmi; Zulkipli, Zulkipli; Candlekie, Candlekie (LPPM Universitas Putera Batam, 2024)
This research is motivated by the management of credit application data management and management of prospective debtor eligibility data and credit scoring data at PT. Bank Perkreditan Rakyat Dana Nusantara, Tanjungpinang City, which does not yet have a computerized system that is integrated between marketing, the assessment section and the team leader. Where each credit application data for each prospective debtor and credit scoring data and verification results are processed and summarized in Microsoft Excel and each application document is still summarized manually. With the conditions and descriptions mentioned above, it is very possible that the data collection process will experience errors and mistakes and even documents can be scattered or lost. So that the marketing and assessment sections concerned have difficulty taking action because the documents have been scattered or lost. Currently, credit application data management is carried out manually, where the process of submitting credit application documents is carried out directly, then the management of prospective debtor data, credit scoring is summarized into Microsoft Excel. As a result, marketing assessments become slower and other work is disrupted. So the author took the initiative to create a system that is able to adequately manage all credit application data management processes using the Waterfall method in designing software that will be used by all users of the designed system. To make it easier and accessible anytime and anywhere, the system is designed based on a website, so that notifications regarding the continuation of the credit application are directly entered and displayed automatically in the system, especially for each prospective debtor who has made a credit application, whether the application is approved or rejected. In designing the system, the author uses PHP (Programing Hypertext Prepocessor), framework (LARAVEL) as a system design media.